The Study of Biosurfactant Stability and The Effect on Lipase Activity - Alvionita, Mieke; Hertadi, Rukman; Fazli, Rahmat Rizki; Dewi, Andi Alfira Ratna Faradisa; Rose, Tasyang Oktavia (Biology, Medicine, & Natural Product Chemistry, 2024)
Lipase is one of hydrolase enzyme that catalyzed hydrolysis reaction of triacylglycerols into free fatty acids and monoglycerides or glycerol. These biocatalysts are widely used in several industries, namely food and pharmaceutical industry. The activity of lipase can increase significantly if the substrate forms an emulsion. Since biosurfactant has been known to have emulsification characteristic, the effect of biosurfactant addition into lipase is necessary to be investigated. It is the first report that evaluate the effect of microbial surfactant on lipase activity. The purpose of this research is to analyze the stability of biosurfactant emulsion under various conditions, such as salinity and pH as well as their potential to enhance lipase activity. Biosurfactant used was Halomonas elongata BK-AG18 from the collection of Biochemistry Research Group ITB, Bandung, Indonesia. It was found that after the addition of NaCl, there was no significant decrease in the emulsification activity of the biosurfactant. The emulsification index (IE24) of biosurfactant with several NaCl concentrations (2, 5, 10, 15, 20, and 25%) was obtained around 50%. Stability test of biosurfactant at pH range 4-10 showed the highest IE24 of biosurfactant was obtained at pH 6. The effect of biosurfactants on lipase hydrolysis activity is also discussed in this article. Lipase hydrolysis activity was tested using p-nitrophenyl palmitate substrate. The highest lipase activity was obtained after the addition of 70% biosurfactant (v/v) at 0.026 units. This study shows that biosurfactant from H. elongata BK-AG18 has the potential to increase lipase activity.